Quantitative Determination and Comparison of the Surface Binding of Phosphonic Acid, Carboxylic Acid, and Catechol Ligands on TiO2 Nanoparticles - Zeininger, Lukas; Portilla Berlanga, Luis; Halik, Marcus; Hirsch, Andreas (Chemistry - A European Journal, 2016)
The adsorption, desorption, co-adsorption, and exchange behavior of phosphonic acid, carboxylic acid, and catechol derivatives on the surface of titanium oxide (anatase) nanoparticles are investigated. Thermogravimetric analysis provides a facile and fast-track quantitative determination of the wet-chemical monolayer adsorption constants and grafting densities of ten adsorbates, all under neutral pH conditions. This characterization protocol allows straightforward quantification of the relevant thermodynamic data of ligand adsorption and a comparison of ligand adsorption strengths. The reported procedure is proposed as a universal tool and it should be applicable to many other colloidal metal oxide materials. Moreover, the determined values for the adsorption constants and the monolayer grafting densities provide a toolbox for the assessment of the adsorbates' behavior in desorption, exchange, and co-adsorption equilibria. This versatile evaluation procedure will help to identify optimal monolayer-surface combinations and to evaluate critical parameters, such as monolayer robustness, ligand exchange rates, or targeted mixed assembly of functionalities.